2021
DOI: 10.3390/v13061015
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Cellular FAM111B by Human Adenovirus C Type 5 E1 Oncogenes

Abstract: The adenovirus type 5 (HAdV-C5) E1 transcription unit encodes regulatory proteins that are essential for viral replication and transformation. Among these, E1A and E1B-55K act as key multifunctional HAdV-C5 proteins involved in various steps of the viral replication cycle and in virus-induced cell transformation. In this context, HAdV-C5-mediated dysregulations of cellular factors such as the tumor suppressors p53 and pRB have been intensively investigated. However, cellular components of downstream events tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…FAM111B is a trypsin-like cysteine/serine peptidase conserved in primates but absent in rodents (17). Interestingly, FAM111B has been described as a restriction factor for human adenovirus type 5 (Ad5) (18) whereas its paralog, FAM111A is a host range factor for SV40 and orthopoxviruses (19,20). We therefore included FAM111A in our analysis, as it is also downregulated in our transcriptome analysis, but with a lower log2 fold change of -0.92.…”
Section: E2f3 Is a Major Regulator Of Fam111a And Fam111b During Mcmv...mentioning
confidence: 99%
See 1 more Smart Citation
“…FAM111B is a trypsin-like cysteine/serine peptidase conserved in primates but absent in rodents (17). Interestingly, FAM111B has been described as a restriction factor for human adenovirus type 5 (Ad5) (18) whereas its paralog, FAM111A is a host range factor for SV40 and orthopoxviruses (19,20). We therefore included FAM111A in our analysis, as it is also downregulated in our transcriptome analysis, but with a lower log2 fold change of -0.92.…”
Section: E2f3 Is a Major Regulator Of Fam111a And Fam111b During Mcmv...mentioning
confidence: 99%
“…While FAM111A is a restriction factor for host range mutants of SV40 and orthopoxviruses (19,20), FAM111B is a restriction factor for Ad5 (18). To identify whether one of these two proteins functions as an MCMV restriction factor, we generated recombinant MCMVs encoding shRNAs specific for FAM111A (MCMV A-sh) or FAM111B (MCMV B-sh), using the same method as described above for CCNE2 (…”
Section: E2f3 Is a Major Regulator Of Fam111a And Fam111b During Mcmv...mentioning
confidence: 99%
“…Furthermore, FAM111B levels rise early and decrease late during human adenovirus infection. 13 However, the mechanisms underlying FAM111B expression and function in ovarian cancer remain unknown. Herein, FAM111B expressions were significantly upregulated in ovarian cancer tissues and various ovarian cancer cell lines.…”
Section: Impact Statementmentioning
confidence: 99%
“…10 12 Furthermore, FAM111B levels rise early and decrease late during human adenovirus infection. 13 However, the mechanisms underlying FAM111B expression and function in ovarian cancer remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to FAM111A, FAM111B does not interact with SV40 LT and has not been implicated in cellular protection from SV40 ( Fine et al, 2012 ). However, a recent study showed that FAM111B is upregulated after infection with human adenovirus and functions as a host restriction factor ( Ip et al, 2021 ), suggesting that FAM111B might be an antiviral factor with different specificity.…”
Section: Fam111b: a Paralog Of Fam111amentioning
confidence: 99%